A dual process model of affective and instrumental implicit attitude, self-monitoring, and sedentary behavior. (September 2022) - Phipps, Daniel J.; Rhodes, Ryan E.; Jenkins, Kailas; Hannan, Thomas E.; Browning, Nicholas G.; Hamilton, Kyra
Abstract: Introduction: A dual process model based upon the affect and health behavior framework was used to explain sedentary behavior, where affective and instrumental components of implicit attitude were measured. Extending dual process theory, we assessed the moderating role of self-monitoring on the effects of implicit attitude on behavior. Method: In Study 1, 148 office workers completed measures of affective and instrumental implicit attitude and self-monitoring at baseline, followed by a measure of sedentary behavior one week later. We then replicated this study in 241 undergraduates, with the addition of measures of the theory of planned behavior at the initial time point to represent conscious pathways to behavior. Results: In both studies there was no direct effect of either form of implicit attitude on behavior. However, self-monitoring moderated the effect of affective implicit attitude such that affective implicit attitude was a significant correlate of sedentary behavior only in those low in self-monitoring. In Study 2, sedentary behavior was also associate with intention, and intention was in turn associated with explicit affective attitude, subjective norm, and perceived behavioral control. Self-monitoring was not associated with sedentary behavior, nor did it moderate the intention-behavior relationship. Discussion: Findings suggest sedentary behavior is a largely affect driven behavior. Further, both reasoned and automatic processes contribute to sedentary behavior, but automatic processes only make a significant contribution when individuals are not consistently monitoring their behavior. Highlights: A dual process model was used to explain sedentary behavior. Self-monitoring was hypothesised to moderate the effects of implicit attitude and intention on behavior. Affective implicit attitude was associated with sedentary behavior in two studies only in those low in self-monitoring. Sedentary behavior was associated with intention.